Anti-gypsyism, racial knowledge and colonial amnesia - Picker, Giovanni (Sociología Histórica, 2020)
This intervention brings together insights from race critical theories and historical sociology to provide a framework for understanding the longstanding racism against Romani people across Europe. It directly draws on Picker's 2017 monograph Racial Cities , and argues that in order to understand the racial segregation of Romani people in Europe, racial knowledge and colonial amnesia should be squarely placed at the core of analytical scrutiny and political intervention. The reason for this is that when looking at several cases of urban authorities' actions on Romani people in 21st-century Europe, key similarities can be detected with colonial authories's actions on "natives" in the cities of European empires.